2022
DOI: 10.7717/peerj.14293
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequences of three Broussonetia species and comparative analysis within the Moraceae

Abstract: Background Species of Broussonetia (family Moraceae) are commonly used to make textiles and high-grade paper. The distribution of Broussonetia papyrifera L. is considered to be related to the spread and location of humans. The complete chloroplast (cp) genomes of B. papyrifera, Broussonetia kazinoki Sieb., and Broussonetia kaempferi Sieb. were analyzed to better understand the status and evolutionary biology of the genus Broussonetia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…The GC content of the IR regions was higher than that of the non-coding intergenic regions because of the presence of rRNA genes [27]. In addition, the number of predicted genes was smaller (127) than that (131) which were previously reported in the F. simplicissima [13], F. concinna [28], and Broussonetia species [29] genomes with 15 intron-containing genes. Several genes are known to possess structural intron variation, such as atpF, rpoC2, rpl12, rps12, and rps16 [2,30].…”
Section: Discussionmentioning
confidence: 73%
“…The GC content of the IR regions was higher than that of the non-coding intergenic regions because of the presence of rRNA genes [27]. In addition, the number of predicted genes was smaller (127) than that (131) which were previously reported in the F. simplicissima [13], F. concinna [28], and Broussonetia species [29] genomes with 15 intron-containing genes. Several genes are known to possess structural intron variation, such as atpF, rpoC2, rpl12, rps12, and rps16 [2,30].…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, we annotated the psbN gene, responsible for encoding the photosystem biogenesis factor 1, as pbf 1. It was observed that the inf A gene, which encodes translation initiation factor 1, underwent pseudogenization, a common occurrence in many members of Moraceae [33][34][35][36]. Utilizing 78 plastid protein-coding genes, we achieved consistent topologies across MP, ML, and BI trees, supported by high bootstrap values and posterior probability (Figure 2).…”
Section: Complete Plastomes Of Figs and Phylogenetic Relationshipsmentioning
confidence: 68%
“…A PR2 Rule bias plot was generated with A3/(A3 + T3) on the x-axis and G3/(G3 + T3) on the y-axis. If the base content of one strand is A = T and G = C, it signifies that mutation pressure and natural selection would not affect both complementary DNA strands [ 59 ]. The center of the plot is set at (0.5, 0.5), where the distance and direction from the center point represent the degree and direction of PR2 bias, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Complete CDSs of HSP20 genes were extracted using TBtools-IIv2.052, ensuring that ATG acted as the start codon and that TGA, TAA, and TAG acted as the stop codons. The relative synonymous codon usage (RSCU), codon adaptation index (CAI), synonymous codon GC content, and 3rd base contents (A3s, T3s, G3s, and C3s) were determined using CodonW 1.4.2 [59]. Codon usage frequencies were calculated with the CUSP tool on the EMBOSS services (https://www.bioinformatics.nl/emboss-explorer/) (accessed on 11 October 2023), while the effective codon numbers were obtained using CHIPS, while the effective codon numbers were obtained using CHIPS.…”
Section: Codon Usage Bias Analysismentioning
confidence: 99%